PERANCANGAN KOMUNIKASI VISUAL PT. SALAM PACIFIC INDONESIA LINES BERBASIS BUDAYA GUNA MENINGKATKAN BRAND AWARENESS - Arif, Muhamad; Budiardjo, Hardman; Riqqoh, Abdullah Khoir (Jurnal Art Nouveau, 2016)
PT. Salam Pacific Indonesia Lines is a shipping company established since 46 years ago. Since the company established, has no visual communication media to support the promotion or introduce the company to the public. One of the promotional activities to introduce the company to the public during this time is a promotional event by participating in the Job Fair event. Thus the need for visual communication media through a media campaign. The objectives of this study is to design the visual communication media PT. Salam Pacific Indonesia Lines based culture to increase brand awareness. The method used is a qualitative method is to conduct interviews, observation. documentation. and literature to get the data used to support the manufacture of visual communication design concepts. From the analysis of data on visual communication design is found keyword